Lutein Exerts Antioxidant and Anti-Inflammatory Effects and Influences Iron Utilization of BV-2 Microglia - Ramóna Pap; Edina Pandur; Gergely Jánosa; Katalin Sipos; Attila Agócs; József Deli (MDPI AG, 2021)
Lutein is a tetraterpene carotenoid, which has been reported as an important antioxidant and it is widely used as a supplement. Oxidative stress participates in many human diseases, including different types of neurodegenerative disorders. Microglia, the primary immune effector cells in the central nervous system, are implicated in these disorders by producing harmful substances such as reactive oxygen species (ROS). The protective mechanisms which scavenge ROS include enzymes and antioxidant substances. The protective effects of different carotenoids against oxidative stress have been described previously. Our study focuses on the effects of lutein on antioxidant enzymes, cytokines and iron metabolism under stress conditions in BV-2 microglia. We performed cell culture experiments: BV-2 cells were treated with lutein and/or with H2O2; the latter was used for inducing oxidative stress in microglial cells. Real-time PCR was performed for gene expression analyses of antioxidant enzymes, and ELISA was used for the detection of pro- and anti-inflammatory cytokines. Our results show that the application of lutein suppressed the H2O2-induced ROS (10': 7.5 ng + 10 µM H2O2, p = 0.0002; 10 ng/µL + 10 µM H2O2, p = 0.0007), influenced iron utilization and changed the anti-inflammatory and pro-inflammatory cytokine secretions in BV-2 cells. Lutein increased the IL-10 secretions compared to control (24 h: 7.5 ng/µL p = 0.0274; 10 ng/µL p = 0.0008) and to 10 µM H2O2-treated cells (24 h: 7.5 ng/µL + H2O2, p = 0.0003; 10 ng/µL + H2O2, p = 0.0003), while it decreased the TNFα secretions compared to H2O2 treated cells (24 h: 7.5 ng/µL + H2O2, p < 0.0001; 10 ng/µL + H2O2, p < 0.0001). These results contribute to understanding the effects of lutein, which may help in preventing or suppressing ROS-mediated microglia activation, which is related to neuronal degeneration in oxidative stress scenario.